Comparison of Wet Mount, Kato-Katz, and Sedimentation Methods in Detecting Soil Transmitted Helminth Infections in Indonesia - Rahim, Adelia Riezka; Triani, Eva; Rosyunita, Rosyunita; Hasbi, Nurmi (Jurnal Biologi Tropis, 2025)
Soil-transmitted helminths (STH) remain highly prevalent in Indonesia and continue to pose a major public health concern, particularly in areas with limited diagnostic capacity. Reliable and cost-effective detection methods are crucial for accurate surveillance and the success of national deworming programs. This study aims to compare three commonly used microscopic techniques (wet mount, Kato-Katz, and sedimentation) to evaluate their diagnostic performance and suitability for use in resource-limited settings through a literature review. Wet mount is rapid and inexpensive but limited by low sensitivity in light infections. The Kato-Katz method, endorsed by the World Health Organization as the gold standard, offers higher sensitivity and enables egg quantification, though its performance decreases when only a single sample is examined. Sedimentation is useful for detecting heavier trematode eggs and is relatively simple to perform, but sensitivity remains a challenge. Overall, while all three techniques are feasible in resource-limited settings, their effectiveness depends on infection intensity, sample handling, and examiner skill. Training and quality control are therefore essential to improve diagnostic accuracy and support ongoing STH control programs in Indonesia.